Association of Timing for Starting Dual Antiplatelet Treatment With Cilostazol and Recurrent Stroke: A CSPS.com Trial Post Hoc Analysis. (8th March 2022) - Toyoda, Kazunori; Omae, Katsuhiro; Hoshino, Haruhiko; Uchiyama, Shinichiro; Kimura, Kazumi; Miwa, Kaori; Minematsu, Kazuo; Yamaguchi, Keiji; Suda, Yoshitaka; Toru, Shuta; Kitagawa, Kazuo; Ihara, Masafumi; et al.
Abstract : Background and Objectives: Long-term treatment with the combination of cilostazol with aspirin or clopidogrel showed a lower risk of stroke recurrence compared to aspirin or clopidogrel alone after high-risk noncardioembolic ischemic stroke in a randomized trial. We aimed to determine whether the effect of the dual medication compared to monotherapy on risk of recurrent ischemic stroke differs according to timing of starting medication after stroke onset. Methods: In a subanalysis of the randomized controlled trial, patients between 8 and 180 days after stroke onset were randomly assigned to receive aspirin or clopidogrel alone or a combination of cilostazol with aspirin or clopidogrel. They were divided into 3 groups according to the timing of starting trial treatment: between 8 and 14 days after stroke onset (8–14 days group), between 15 and 28 days after stroke onset (15–28 days group), and between 29 and 180 days after stroke onset (29–180 days group). The primary efficacy outcome was the first recurrence of ischemic stroke. Safety outcomes included severe or life-threatening bleeding. Results: Of 1, 879 patients, 498 belonged to the 8–14 days group, 467 to the 15–28 days group, and 914 to the 29–180 days group. There was a significant treatment-by-subgroup interaction for the recurrence of ischemic stroke between trial treatment and trichotomized groups. The recurrence of ischemic stroke was less common with dual therapy than with monotherapy in the 15–28 days group (annualized rate 1.5% vs 4.9%, respectively; adjusted hazard ratio 0.34 [95% CI 0.12–0.95]) and the 29–180 days group (1.9% vs 4.4%, respectively; 0.27 [0.12–0.63]) and similarly common in the 8–14 days group (4.5% for both; 1.02 [0.51–2.04]). Severe or life-threatening bleeding occurred similarly between patients on dual therapy and those on monotherapy in any of the trichotomized groups (crude hazard ratio 0.22 [95% CI 0.03–1.88] in the 8–14 days group, 1.07 [0.15–7.60] in the 15–28 days group, and 0.76 [0.24–2.39] in the 29–180 days group). Discussion: Long-term dual antiplatelet therapy using cilostazol starting 15–180 days after stroke onset, compared to therapy started 8–14 days after onset, was more effective for secondary stroke prevention than monotherapy without increasing hemorrhage risk. Trial Registration Information: ClinicalTrials.gov NCT01995370; UMIN Clinical Trials Registry 000012180. Classification of Evidence: This study provides Class II evidence that for patients with acute noncardioembolic stroke taking either aspirin or clopidogrel, the addition of cilostazol 15–180 days after stroke onset decreases the risk of recurrent ischemic stroke.